VALIDASI SKALA DUKUNGAN SOSIAL DAN IMPLIKASINYA TERHADAP PENYESUAIAN AKADEMIK - Arnes Meilenda; Neneng Tati Sumiati; Ibnu Athoilah (Qiro'ah : Jurnal Pendidikan Agama Islam, 2024)
Social support can be a way to foster academic excellence through academic adjustment. To understand how empirically social support can be an antecedent of terrific academic adjustment, we need to test the validity of the scale measuring social support. Sample in this study was taken from population of graduate students at University of Pamulang and Uin Syarif Hidayatullah, with a total of 402 respondents. Confirmatory factor analysis and multiple linear regression were conducted to examine social support scale validity and its role as an antecedent of academic adjustment. Multidimensional model of social support is fit with several modifications to the model with RMSEA = 0.043 and 10 items are valid to measure social support. Social support significantly predicts academic adjustment with R2 = 0.039. One of three dimensions of social support, namely family support, significantly predicts positive academic adjustment which indicates the importance of family presence for graduate students.